Evaluasi Tingkat Toleransi 35 Genotipe Kakao terhadap Periode Kering - Towaha, Juniaty; Wardiana, Edi (Jurnal Tanaman Industri dan Penyegar, 2015)
A prolong dry periods could have a negative impact on growth and yield of cocoa. The objectives of this study were to evaluate the tolerance levels of 35 cocoa genotypes to dry periods. The study was conducted at the Pakuwon Experimental Station, Indonesian Industrial and Beverages Crops Research Institute, Sukabumi, West Java; 450 m above sea level; Latosol soil type; and B type of climate; started from August 2014 until October 2015. Thirty five cacao genotypes consisted of two released variety  (i.e Sulawesi 1 and SCA 6) and 33 other genotypes were used in this research.  The cacao plants were three-years old, cultivated at a 3 x 3 m spacing distance under the 26 years old Salak Dwarf coconut trees.  Ten plant samples were determined randomly and the fruits were harvested in February 2015 (wet period) and October 2015 (dry period). A bulk of 10–30 pods per genotype were randomly selected for each harvest periods. The variable observed were fresh weigth per pod,  number of beans per pod, fresh and dry weight of beans per pod, and fresh weight of pod husks + pulps per pod. The tolerance level to dry periods was determined base on the dry weight of bean/pod.  The result showed that a continueous six months dry periods prior to harvesting significantly reduced yield components from 4.92%-42.54%.  Based on the dry weight of beans per pod, three genotypes, namely KW 162, KW 165, and KW 215, were classified as tolerant, while the other were moderately tolerant and susceptible to drought. The result implies the important of further research to obtain superior cocoa clones resistance to drought.